PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MELALUI TEKNIKCOOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) SISWA KELAS V SEKOLAH DASAR SUKOSARI 02 KABUPATEN MADIUN - Katiman, Katiman (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2018)
The ability to read comprehension of adequate and regular practice. But in the belief, the ability to read the understanding of grade V students in Sukosari 02 primary school is still low. There are three things that become the focus of this research (1) prabalu stage, (2) stage when reading, and (3) pascabaca. This study used a qualitative approach with excel classroom action research. Increased reading comprehension ability at pre-reading stage in cycle I obtained the average class 65,31, and in cycle II increased to 70,62. While improving the ability to read comprehension at the stage when reading cycle I the average number of class 69, and in cycle II increased to 75. Increased ability to read the definition of publication on pascabaca that is in cycle I obtained average class 69.01 and in cycle II increased to 76.04. From the data, it can be concluded that CIRC technique can improve students' reading comprehension comprehension in all reading stages.